(3HMhK GdYedjGJ (B(2) ((3c(B13) /s - (3Zfje, MSjf YWGs ((3GdbGgQI(B: s (3eWHYI eQcR GdJYdje GdeaJhM(B, s, 1994)
(3MGdGJ YedjI dGSJNOGeGJ GdHQeLI GdNWjI, GdJYHjQ Yf LOhd GdSeHdcS aj Tcd eUahaGJ, fXQjI GdKfGFjI,GdHQGeL GdOjfGejcjIs
(3edGMb U(B..242 s
Keywords: (3GdeUahaGJs; (3HMhK GdYedjGJs